Effective implementation of Article 5.3 of the WHO framework convention on tobacco control to curb tobacco industry interference - Rakesh Gupta; Anjali Bhawra; Varun Roojam; Rajiv Bhalla (Tobacco Induced Diseases, 2018)
Background and challenges to implementation The tobacco industry has historically employed a multitude of tactics to shape and influence tobacco control policy. In Punjab, Officials at various levels have been approached by representatives of Tobacco Industry for easing implementation of Cigarettes and Other Tobacco Products Act 2003 and withdrawing certain notifications to tackle Tobacco/Nicotine menace. Industry has used its economic power, lobbying and marketing machinery, and manipulation of the media to discredit scientific research and influence governments in order to propagate the sale and distribution of its deadly product.It goes to the credit of political leadership and bureaucracy that most of their attempts have been foiled. The objective of the study was to assess effective implementation of Article 5.3 of the WHO Framework Convention on Tobacco Control.